Um estudo sobre bullying como forma de reprodução da violência - Maicom Marques de Paula (2016)
Complex, historical and social fact multicausal, violence found in different spaces of social interaction, fertile ground for their production and reproduction. Studies on the occurrence of violence between children and adolescents, as well as of young people in their processes of socialization has been increasing prominence in the national and international scene, given the peculiar condition of development of these. Among the various forms of violence that manifest themselves in this population group, the bullying, violent behavior, without apparent motivation, repetitive, intentional, characterized by the imbalance of power between the people involved, whose losses make it a public health problem. Considering the theme concerned, the present study investigated the prevalence of bullying among teenagers of the municipality of Betim MG and its relationship with the social reproduction of violence. Based on the theoretical, aimed to study the phenomenon in the light of the concept of violence and social and historical context in which it operates. Initially took a literature review followed by the presentation of an article whose results showed high prevalence of bullying among teenagers, identified the profiles of those involved, correlated to sociodemographic aspects such as sex, race/color, and age. It has also identified the ways and places of occurrence. In addition, the study pointed out the correlation between bullying, domestic violence and social violence reinforcing the hypothesis of the phenomenon while playing the violence suffered in other spaces. Accordingly, it was concluded that the intervention strategies forward occurrences of bullying must overcome the simplistic vision of the phenomenon, the individual characteristics of the involved and expand to expanded proposals, considering the family and social context.